Successful management of a patient with toxic epidermal necrolysis by high dose intravenous immunoglobulin. Issue 4 (2013) - Güneş, Ali; Yolbaş, İlyas; Kelekçi, Selvi; Yel, Servet; Şahin, Cahit; Ece, Aydın
No abstract available